KINERJA USAHATANI KOMODITAS WORTEL (Daucus carrota L) (Studi kasus di Kabupaten Cianjur, Propinsi Jawa Barat) - Ade Supriatna (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2008)
The Performance of Carrot (Daucus carrota L) Farming (a case study in Cianjur Regency, West Java Province). Approaching the era of globalization, the government is demanded to improve the performance of vegetable farming to be more competitive in both domestic and international markets. This study was conducted in 2005 in West Java. The objectives of the study were: (a) to identify the characteristics of carrot farmers, (b) to identify cultivation practices, (c) to analyze the economic feasibility of carrot farm, and (d) to describe the marketing channels, margin and price share received by farmers. The results show that the farmer's characteristics were sufficiently good in the aspects of age, education and participation in trainings, but some aspects were still weak such as small farm size (0.44 ha/farmer) and 22.2 % of farmers of hired status. Vegetable farm required a cost of Rp.28.8 million, a gross income of Rp.53.4 million and a net income of Rp.25.4 million/ha/year. It was suitable economically with B/C ratio of 1.89. The main problem in the production was selling price uncertainty, so that the farmers were unsure to implement the recommended technologies, especially the application of fertilizers. There were three channels in marketing carrots from farmers to consumers, i.e. (1) farmer, collector trader, whole trader, central market, traditional market, consumer; (2) farmer, collector trader, Sub terminal agribusiness (STA), central market, traditional market, consumer and (3) farmer, collector trader, supplier, super market, consumer. The farmers sold the carrot product through the first channel (76.6%), the second channel (13.3%) and the third channel (10.1%). The first and the second channels gave farmer's share of 49.3%, marketing cost of Rp.172 and a marketing profit of Rp.370/kg. While the third cannel gave farmer's share of 20.9%, marketing cost of Rp.300 and marketing profit of Rp.553/kg. The central market was the referee market, the price offered by the central market would be used as the standard to determine the purchasing price by the preceding market institutions until the farmers. Up till now, the selling prices of vegetables are very fluctuated and unpredictable causing the farmers to be doubtful to implement the technologies advised by the government to maintain the balance of supply and demand in the central market so the farmers can obtain selling price certainty. Key words: carrot, farm performance, West Java. Dalam menyongsong era globalisasi, pemerintah dituntut meningkatkan kinerja usahatani sayuran agar lebih kompetitif baik di tingkat pasar domestik maupun pasar intemasional. Penelitian ini dilaksanakan tahun 2005 di Propinsi Jawa Barat. Tujuan penelitian adalah; (a) mengidentifikasi karakteristik petani, (b) praktek budidaya, (c) menganalis kelayakan ekonomi usahatani dan (c) menggambarkan saluran pemasaran, margin dan bagian harga yang diterima petani. Hasil menunjukan bahwa karakteristik petani cukup baik dalam aspek umur, pendidikan dan keikutsertaan pelatihan tetapi beberapa aspek masih lemah yaitu rataan penguasaan lahan masih rendah (0,44 ha/petani) dan masih ditemukan petani berstatus sewa sebanyak 22,2%. Usahatani sayuran membutuhkan biaya Rp.28,8 juta, penerimaan kotor Rp.53,4 juta dan penerimaan bersih 25,4 juta /ha/tahun. Usahatani sayuran termasuk layak secara ekonomi dengan nilai B/C 1,89. Masalah utama dalam produksi adalah ketidakpastian harga jual sayuran sehingga petani masih ragu untuk menerapkan budidaya sesuai rekomendasi,terutama penggunaan pupuk. Ditemukan tiga saluran pemasaran wortel dari petani sampai ke konsumen, yaitu; (1) petani, pedagang pengumpul, pedagang besar, pasar induk, pasar tradisional, konsumen; (2) petani, pedagang pengumpul, Sub terminal agribisnis (STA), pasar induk, pasar tradisional, konsumen dan (3). Petani, pedagang pengumpul, suplayer, super market, konsumen. Petani menjual wortel melalui saluran pertama (76,6%), saluran kedua (13,3%) dan saluran ketiga (10,1%). Farmer's share saluran pertama dan kedua adalah 49,3%, biaya pemasaran Rp.172,- dan keuntungan pemasaran Rp.370,-/kg. Sedangkan farmer's share saluran ketiga adalah 20,9%, biaya pemasaran Rp.300,- dan keuntungan pemasaran Rp.553,-/kg. Pasar induk merupakan pasar acuan (referee market), harga beli wortel yang ditetapkan pasar tersebut dijadikan acuan untuk menetapkan harga bell oleh pelaku pasar sebelumnya sampai di tingkat petani. Selama ini, harga jual sayuran sangat fluktuatif dan sulit diperkirakan menyebabkan petani ragu-ragu untuk menerapkan teknologi sesuai anjuran Pemerintah harus mengatur keseimbangan suplai dan deman produk sayuran di pasar induk agar supaya petani memperoleh kepastian harga jual. Kata kunci: wortel, kinerja usahatani, Jawa Barat.